HEAVY METAL CADMIUM (Cd) AND LEAD (Pb) IN VANAME SHRIMP (Litopenaeus vannamei) COLLECTED FROM TRADITIONAL MARKETS IN MEDAN CITY, INDONESIA - Yusni, Eri; Setiani, Tri Pardiana (AQUASAINS, 2019)
The presence of heavy metals in the aquatic environment must be monitored continuously. This study aims to determine the amount of heavy metal content of Cadmium (Cd) and Lead (Pb) on Vaname Shrimp (Litopenaeus vannamei). Determining the value of Cadmium (Cd) and Lead (Pb) using an AAS (Atomic Absorption Spectrophotometer) device. It is known that the highest Cd content in the sample 4 (market pancing) which is worth 0.011 mg/kg, and the lowest is in the sample 6 (market sei kambing) which is worth 0.004 mg/kg. The value of the highest Pb value is found in the sample 3 (market merah) worth 0.019 and the lowest value is the sample 5 (market petisah) worth 0.008. So that the results of these tests can be concluded, that the content of heavy metals Cd and Pb in each sample of vaname shrimp is classified as low according to the World Health Organization (WHO), namely the maximum limit of Cd is 5.0 and the maximum limit of Pb is 2.0 while according to EUROPEAN UNION the limit of calcium Cd is 0.2 and the maximum limit of Pb is 0.5 because the vaname shrimp sample is still safe for consumption and can be an export commodity.